Social Media Marketing Strategy Proposal To Improve Brand Awareness Of Zenius Education : (Case Study Of Post-Restructuring And Transition To Zenius.Net) - Aryanti, Aulia Azzahra; Dalimunthe, Gallang Perdhana (Jurnal Economic Resource, 2025)
Digital marketing is a key lever shaping consumer behavior in today’s attention economy, and social media especially Instagram, TikTok, and YouTube has become the primary discovery engine for education brands. This study analyzes how social media led digital marketing affects brand awareness and downstream purchase intentions for Zenius Education. Using a qualitative method, we ran an in depth interview with the Marketing Manager of Zenius Education. Results show that relevant, bite-sized content and direct brand learner interaction (comments, DMs, polls, lives) significantly influence purchase decisions while lifting brand recall and recognition. Social media promotions deliver low-cost reach beyond geographic constraints and effectively move audiences from mere attention to interest and provided the content with outcome first (problem→fix), consistently branded, and posted with a clear cadence. For Zenius, the strongest gains appear when content pairs conceptual teaching clarity with short-form formats and is tied to conversion paths (e.g., mock tests, trials) plus community touchpoints (WhatsApp/Discord). The results provide key learnings that Zenius can apply to develop a more efficient and measurable approach to rebuild their Gen Z-based brand presence on social media in Indonesia